Certificate physical and human geography - Leong, Goh Cheng (New Delhi Oxford University Press, 1974)
Certificate Physical And Human Geography covers various geographical concepts that are essential for a good understanding of the subject. This book is a good choice for preparing for competitive exams like CSAT.Certificate Physical And Human Geography provides coverage of fundamental concepts regarding the earth s topology, the weather and climate, the different climatic regions, and vegetation across the planet. The book is divided into two parts, Physical Geography, and Weather, Climate and Vegetation. Physical Geography covers the various landforms and coastal regions. The second part covers climate and weather related concepts. Physical Geography begins by examining The Earth and its place in the Universe. It then goes on to explore the Earth s Crust. Then the book looks at the effects that various natural forces have on the Earth s surface. The book covers natural phenomena like Volcanoes and Earthquakes. It discusses the Weathering Process, Mass Movement, and Groundwater. It proceeds on to cover different landforms and the forces that shaped them. It looks at Desert Landforms, Landforms Made By Running Water, Limestone and Chalk Landforms, and Landforms of Glaciation. It also examines Coastal Landforms, The Oceans, Lakes, Islands and Coral Reefs. The Weather, Climate and Vegetation section covers the concepts of Climate and Weather. It then focuses on different weather conditions and climate zones. It discusses the Hot, Wet Equatorial Climate. It also covers the Tropical Monsoon and Tropical Marine Climates. It looks at desert regions like the Hot Desert and Mid-Latitude Desert Climates. It also focuses on The Savanna or Sudan Climate, The Temperate Continental (Steppe) Climate, and The Mediterranean or Warm Temperate Western Margin Climate. Certificate Physical And Human Geography then covers cool climate zones. It discusses the Siberian or Cool Temperate Continental Climate, The Chinese type of climate or Warm Temperate Eastern Margin Climate. The book then focuses on the Laurentian or The Cool Temperate Eastern Margin Climate, the British or Cool Temperate Western Margin Climate and The Arctic or Polar Climate. This book covers the physical topography of the planet, the landforms and the oceans, rivers and lakes. This comprehensive coverage helps the readers understand the dynamic nature of the planet, and the forces that shape it. It also discusses the vastly different climate conditions that prevail in different geographical parts of the planet. It is a good textbook to help students understand the fundamental concepts of physical geography and the weather and climate. It is also a good preparation material for exams like the Civil Services Preliminaries. The book contains numerous illustrations, maps, diagrams and photographs that complement the text, and each chapter also ends with a questions section to test comprehension of the concepts covered.
Keywords: NON TECHNICAL BOOKS (NTB)